Realignment, region, and race : presidential leadership and social identity - Goethals, George R. (Emerald Publishing Limited, 2018)
The Trump presidency may well be the first phase of a new American political alignment deeply rooted in identity politics. Now more than ever, it seems especially important to understand how leaders compete to engage different human motivationshow presidents, presidential candidates, and other political leaders appeal to potential followers needs for economic well-being, safety, self-esteem, and a sense of significance. It is time to come to terms with the roles of race and region in US political history.In 'Realignment, Region, and Race', George R. Goethals addresses this challenge head-on, exploring the place of racial dynamics in American politics from Abraham Lincoln to Donald Trump. He integrates psychology and historical understandings of presidential leadership and politics to explain the way the politics of racial justice and needs for positive social identity have led to different regions in the United States changing party affiliation. He describes the realignment by region of the two major political parties in the United States, the Democrats and Republicans, between the Civil War and the present day, and he considers how for over a century and a half the two parties have offered different social identities, often related to race, that appeal to powerful motives for self-esteem and significance. Goethalss findings uncover deep contexts for understanding how current political leaders engage experiences and attitudes towards African Americans, Hispanic Americans, and Asian Americans in order to tell particular stories about American and regional identities. 'Realignment, Region, and Race' is essential reading for students of politics, history, and psychology, and it is of keen interest to anyone concerned with the power that identity politics has taken on in recent American elections.
Includes index.
Keywords: Political leadership -- United States -- History.; Presidents -- United States -- Racial attitudes -- History.; United States -- Race relations -- Political aspects -- History.; Identity politics -- United States.; Juvenile nonfiction, Social Science, Politics & Government.; Economics.; elektronické knihy; electronic books